Polyhydroxyalkanoate fiber and microfluidic preparation method thereof

Through microfluidic spinning technology and physical blending method, the spinning of polyhydroxy fatty acid ester (PHA) solves the processing difficulties caused by the temperature sensitivity of PHA materials, and improves the mechanical properties and forming efficiency of the fibers.

CN119736734AActive Publication Date: 2025-04-01SUZHOU UNIV
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411919228.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-04-01
Estimated Expiration
2044-12-25

AI Technical Summary

Technical Problem

Due to temperature sensitivity, polyhydroxy fatty acid ester (PHA) materials are difficult to process into fibers, and the existing spinning methods have problems such as low mechanical properties and harsh processing conditions.

Method used

PHA is spinned by microfluidic spinning technology, and physically blended with polylactic acid (PLA) to improve the mechanical properties of the fibers, and use dichloromethane as a solvent to simplify the spinning process.

Benefits of technology

The efficient forming of PHA fibers is achieved, the influence of temperature on fiber formation is avoided, the break strength and elongation of the fibers are improved, and the operation is simple and cost-effective.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119736734A_ABST
    Figure CN119736734A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of fiber preparation, and particularly relates to a polyhydroxyalkanoate fiber and a microfluidics preparation method thereof. The microfluidics preparation method comprises the following steps: respectively preparing a PHA solution and a PLA solution; the PHA solution is obtained by adding polyhydroxyalkanoate into dichloromethane and heating; the PLA solution is obtained by adding dichloromethane into polylactic acid; mixing the PHA solution and the PLA solution to obtain a spinning solution; performing micro-fluidic spinning on the spinning solution, and drying to obtain the polyhydroxyalkanoate fiber, the coagulating bath of the micro-fluidic spinning is selected from ethanol. A simple micro-fluidic spinning process is adopted, a high-voltage power supply or large equipment is not needed in the spinning process, operation is easy, convenient and safe, and prepared fibers are uniform in evenness and good in mechanical property; the spinning method is adopted, so that the fibers are not influenced by temperature in the forming process, and the problem of difficult processing and forming caused by temperature sensitivity of materials is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of fiber preparation, and in particular relates to a polyhydroxyalkanoate fiber and a microfluidic preparation method thereof. Background Art

[0002] Polyhydroxyalkanoate (PHA) is a general term for a class of high-molecular polyesters synthesized by microorganisms. Its molecular structure is a linear hydroxyl-containing alkanoate, which is produced by microbial fermentation. Compared with other degradable materials, it has the environmentally friendly characteristics of being non-fossil prepared and degradable in seawater.

[0003] Since PHA materials are easily degraded by heat and their decomposition temperature is close to the processing temperature, they are difficult to process and shape, and it is even more difficult to process them into fibers. The research on the formation of polyhydroxyalkanoate fibers and their blended fibers is currently mainly carried out through electrospinning, dry spinning or conventional melt spinning, and there are few studies on the wet spinning method. Secondly, since the crystallization rate of polyhydroxyalkanoates is relatively slow, it is easy to cause adhesion between rollers during the melt spinning process, and the spinnability is poor, which limits the fiber formation of polyhydroxyalkanoates, especially the development of industrial preparation of polyhydroxyalkanoate fibers. Therefore, it is very necessary to provide a spinning technology for polyhydroxyalkanoate fibers.

[0004] As a wet spinning method, microfluidic spinning technology can accurately control and manipulate the flow of microscale liquids in microchannels. It has high precision and freedom, breaking the limitation of existing spinning methods that it is difficult to micromanipulate fibers. Compared with the commonly used spinning process, microfluidic spinning can be carried out at room temperature and pressure. It has the advantages of short production process, low environmental requirements, high spinning efficiency, and low energy consumption. It has good application prospects in the development of new biomass fibers and functional fibers. The microfluidic spinning technology is used to spin PHA, which is easy to operate and low in cost, and can avoid the influence of temperature on fiber formation.

[0005] At present, there are three main spinning methods for PHA fibers: electrospinning, melt spinning and dry spinning.

[0006] 1. Electrospinning

[0007] At present, electrospinning is one of the main means of preparing PHA fibers. PHA can be dissolved in solvents such as chloroform and N,N-dimethylamide. The polymer solution is spray-spun in a strong electric field to produce polymer fibers. Using the electrospinning process, PHA nanofibers can be prepared. Nanofibers have special properties such as large specific surface area and small pore size. However, electrospinning generally produces irregularly arranged nanofiber mats, and their mechanical properties are often lower than those of conventional fibers. Patent CN 104452107A discloses a method for preparing a highly elastic polyhydroxyalkanoate porous fiber material. The main steps are to add polyhydroxyalkanoate to a mixed solvent of chloroform and acetone under stirring conditions, stir to obtain a uniform polyhydroxyalkanoate electrospinning stock solution, transfer the spinning stock solution to a glass syringe, fix it on an electrospinning device for electrospinning, collect the obtained fiber membrane and vacuum dry it at 40-60°C for 6-12h to prepare a polyhydroxyalkanoate porous fiber membrane with high elastic properties, and its breaking elongation can reach more than 500%, but the tensile strength is still insufficient, such as Figure 1 shown.

[0008] 2. Melt spinning

[0009] The process of extruding a spinnable polymer from the spinneret holes at a temperature above its melting point, cooling and thinning it into a filamentous solid, and winding it at the same time is called melt spinning. The melting temperature of PHA is 165℃-180℃. When the heating temperature is 10℃ higher than the melting point (180℃), cracking will occur, making the processing temperature range of PHA very narrow; the filaments ejected from the spinneret holes solidify slowly and are easy to stick together, making it difficult to separate the filaments and difficult to unwind after winding. Therefore, the spinning conditions of melt spinning are relatively harsh and difficult to achieve under general experimental conditions.

[0010] 3. Dry spinning

[0011] Dry spinning is a process in which a polymer solution is squeezed from a spinneret into a forming channel, in which hot air is blown into the channel to evaporate the solvent, and the resulting silk thread is curled at a certain speed. During dry forming, the evaporation of the solvent causes the polymer to undergo desolvation, and the fluidity of the stream drops sharply, causing it to turn into a solid state. The PHA fibers made by dry spinning have plastic deformation properties after being formed, and can be stretched and post-treated to obtain fibers with better properties. However, the storage time of the nascent fibers must be strictly controlled, otherwise they will become brittle and will not be able to be post-stretched. Zhu Shuqi and others used a 16% PHBV / chloroform solution to dry-spin fibers. The nascent fibers were stretched 2-5 times at 70°C and then heat-set at 120°C for a fixed elongation. After stretching and post-treatment, the breaking strength of the PHBV fiber was 0.6-1.8 cN / dtex, and the breaking elongation was 40-95%. Figure 2 shown.

[0012] The current prior art has the following defects:

[0013] 1. The melting temperature of PHA is close to the thermal degradation temperature, which is only about 20°C away. It is extremely sensitive to temperature. Therefore, the processing temperature of melt spinning is relatively narrow. However, PHA has a low melting point and slow cooling, so it is easy to double the yarn during spinning, which makes unwinding difficult.

[0014] 2. PHA has high crystallinity and serious post-crystallization phenomenon, and the breaking strength of pure PHA fiber is relatively low;

[0015] 3. When using electrospinning, a high voltage power supply is used, and the mechanical properties of the spun fibers are often lower than those of conventional fibers. Summary of the invention

[0016] In order to solve the problem of difficult processing and forming caused by the temperature sensitivity of PHA, a microfluidic spinning method is used to avoid the influence of temperature on the spinning process and fiber formation, and no high-voltage power supply or large equipment is required. The operation is simple and the cost is low. In order to improve the mechanical properties of PHA fibers, PHA is modified and physically blended with polylactic acid (PLA) for spinning. The process is simple and the effect is good.

[0017] In order to solve the above-mentioned technical problems, this application provides the following technical solutions:

[0018] The present invention provides a microfluidic preparation method for polyhydroxyalkanoate fibers, wherein the spinning process is safe and simple, and comprises the following steps:

[0019] S11: preparing PHA solution and PLA solution respectively;

[0020] The PHA solution is obtained by adding polyhydroxyalkanoate (PHA) into dichloromethane and heating at 50-80° C. for 4-8 hours; the PLA solution is obtained by adding polylactic acid (PLA) into dichloromethane;

[0021] S12: mixing the PHA solution and the PLA solution to obtain a spinning solution;

[0022] S13: performing microfluidic spinning on the spinning solution and drying to obtain the polyhydroxyalkanoate fiber; the coagulation bath of the microfluidic spinning is selected from ethanol, and the extrusion rate is 1-3 mL / h.

[0023] Preferably, the PHA is selected from P34HB (poly-3-hydroxybutyrate-4-hydroxybutyrate) or PHB (poly-3-hydroxybutyrate).

[0024] Preferably, in step S11, polyhydroxyalkanoate and polylactic acid are added to dichloromethane under stirring conditions, and mixed by magnetic stirring.

[0025] Preferably, in the PHA solution, the concentration of the solute is 2-8 wt %.

[0026] Preferably, in the PLA solution, the concentration of the solute is 8-12 wt %.

[0027] Preferably, in step S11, condensation reflux is used during heating, and stirring is performed.

[0028] Preferably, in step S11, the PLA solution is obtained by adding dichloromethane to polylactic acid (PLA) and stirring the mixture at room temperature (25±5° C.) for 4-8 hours.

[0029] Preferably, in the spinning solution, the volume ratio of polyhydroxyalkanoate to polylactic acid is 1-2:1-2.

[0030] Furthermore, in the spinning solution, the volume ratio of polyhydroxyalkanoate to polylactic acid is 1:1, 1:2 or 2:1.

[0031] Preferably, in step S12, the mixing method is stirring for 30-60 minutes, ultrasonic dispersion for 30-60 minutes, and magnetic stirring for 30-60 minutes at room temperature.

[0032] Preferably, in step S13, the microfluidic spinning is followed by drying at room temperature.

[0033] The present invention also provides a polyhydroxyalkanoate fiber prepared by the preparation method, and the fiber has high breaking strength and breaking elongation.

[0034] The technical solution of the present invention has the following advantages over the prior art:

[0035] 1. The present invention adopts a simple microfluidic spinning process, which does not require a high-voltage power supply or large equipment during the spinning process. The operation is simple and safe, and the prepared fiber strands are relatively uniform and have good mechanical properties.

[0036] 2. The spinning method used makes the fiber unaffected by temperature during the forming process, thus avoiding the problem of difficult processing and forming caused by the temperature sensitivity of the material;

[0037] 3. Dichloromethane is used as the solvent, which is much less toxic than the commonly used chloroform and is safer. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 The tensile curves of the fiber membranes electrospun at different mass ratios of acetone and chloroform.

[0039] Figure 2 The stress-strain curves of dry-spun PHBV nascent fibers and fibers stretched at different ratios after heat treatment.

[0040] Figure 3 This is the tensile curve of P34HB / PLA fiber at different spinning speeds.

[0041] Figure 4 Optical microscope image (a) and scanning electron microscope image (b) of PHB / PLA fibers with a volume ratio of 1:2. DETAILED DESCRIPTION

[0042] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments so that those skilled in the art can better understand the present invention and implement it, but the embodiments are not intended to limit the present invention.

[0043] Example 1

[0044] Weigh 1g of P34HB powder, slowly add the weighed P34HB to 49g of dichloromethane solvent, transfer the mixed solution to a round-bottom flask with a condensation reflux device for stirring, heat to 60°C during stirring, stir for about 6 hours to obtain a P34HB solution. Weigh 6g of PLA particles, slowly add the weighed PLA to 44g of dichloromethane solvent, and magnetically stir at room temperature for about 6 hours to obtain a PLA solution. Measure 4mL of P34HB solution and 8mL of PLA solution, blend them, magnetically stir for 30min at room temperature, use ultrasonic dispersion for 40min, and then magnetically stir for 30min to obtain a spinning solution. Transfer the spinning solution to a plastic syringe, use anhydrous ethanol as a coagulation bath, and perform microfluidic spinning at an extrusion speed of 1.5mL / h. The obtained fiber is dried at room temperature. The average diameter of the fiber obtained under this condition is 49.13μm, and the elongation at break is as high as 400% ( Figure 3 ).

[0045] Example 2

[0046] Weigh 1g of P34HB powder, slowly add the weighed P34HB to 49g of dichloromethane solvent, transfer the mixed solution to a round-bottom flask with a condensation reflux device for stirring, heat to 60°C during stirring, stir for about 6 hours to obtain a P34HB solution. Weigh 6g of PLA particles, slowly add the weighed PLA to 44g of dichloromethane solvent, and stir magnetically at room temperature for about 6 hours to obtain a PLA solution. Measure 4mL of P34HB solution and 8mL of PLA solution, blend them, stir magnetically for 30min at room temperature, disperse them ultrasonically for 40min, and then stir magnetically for 30min to obtain a spinning solution. Transfer the spinning solution to a plastic syringe, use anhydrous ethanol as a coagulation bath, and perform microfluidic spinning at an extrusion speed of 2mL / h. The obtained fibers are dried at room temperature. The average diameter of the fibers obtained under this condition is slightly increased to 51.69μm, the strip uniformity is good, and the breaking strength is high ( Figure 3 ).

[0047] Example 3

[0048] Weigh 1g of P34HB powder, slowly add the weighed P34HB to 49g of dichloromethane solvent, transfer the mixed solution to a round-bottom flask with a condensation reflux device for stirring, heat to 60°C during stirring, stir for about 6 hours to obtain a P34HB solution. Weigh 6g of PLA particles, slowly add the weighed PLA to 44g of dichloromethane solvent, and magnetically stir at room temperature for about 6 hours to obtain a PLA solution. Measure 4mL of P34HB solution and 8mL of PLA solution, blend them, magnetically stir for 30min at room temperature, use ultrasonic dispersion for 40min, and then magnetically stir for 30min to obtain a spinning solution. The spinning solution was transferred to a plastic syringe, and microfluidic spinning was performed with anhydrous ethanol as a coagulation bath at an extrusion speed of 2.5mL / h. The obtained fibers were dried at room temperature. Under this condition, the average diameter of the fibers obtained continued to increase to 67.34μm, while the breaking strength decreased ( Figure 3 ).

[0049] Example 4

[0050] Weigh 1g of PHB powder, slowly add the weighed PHB to 49g of dichloromethane solvent, transfer the mixed solution to a round-bottom flask with a condensation reflux device for stirring, heat to 60°C during stirring, and stir for about 6 hours to obtain a PHB solution. Weigh 6g of PLA particles, slowly add the weighed PLA to 44g of dichloromethane solvent, and magnetically stir at room temperature for about 6 hours to obtain a PLA solution. Measure 4mL of PHB solution and 8mL of PLA solution, blend them, magnetically stir for 30min at room temperature, use ultrasonic dispersion for 40min, and then magnetically stir for 30min to obtain a spinning solution. Transfer the spinning solution to a plastic syringe, use anhydrous ethanol as a coagulation bath, and perform microfluidic spinning at an extrusion speed of 2mL / h. The obtained fibers are dried at room temperature. The fiber strips obtained under this condition have good uniformity ( Figure 4 ).

[0051] Obviously, the above embodiments are merely examples for clear explanation and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the protection scope of the invention.

Claims

1. A microfluidic preparation method for polyhydroxyalkanoate fibers, characterized in that: The steps include: S11: preparing PHA solution and PLA solution respectively; The PHA solution is obtained by adding polyhydroxyalkanoate to dichloromethane and heating at 50-80° C. for 4-8 hours; The PLA solution is obtained by adding dichloromethane to polylactic acid; S12: mixing the PHA solution and the PLA solution to obtain a spinning solution; S13: performing microfluidic spinning on the spinning solution and drying to obtain the polyhydroxyalkanoate fiber; the coagulation bath of the microfluidic spinning is selected from ethanol, and the extrusion rate is 1-3 mL / h.

2. The preparation method according to claim 1, characterized in that In the step S11, polyhydroxyalkanoate and polylactic acid are added into dichloromethane under stirring conditions, and are mixed by magnetic stirring.

3. The preparation method according to claim 1, characterized in that: In the PHA solution, the polyhydroxyalkanoate is selected from poly-3-hydroxybutyrate-4-hydroxybutyrate or poly-3-hydroxybutyrate, and the concentration of the solute is 2-8wt%.

4. The preparation method according to claim 1, characterized in that: In the PLA solution, the concentration of the solute is 8-12 wt %.

5. The preparation method according to claim 1, characterized in that: In the step S11, condensation reflux is used during heating, and stirring is performed.

6. The preparation method according to claim 1, characterized in that: In the step S11, the PLA solution is obtained by adding dichloromethane to polylactic acid and stirring at room temperature for 4-8 hours.

7. The preparation method according to claim 1, characterized in that: In the spinning solution, the volume ratio of polyhydroxyalkanoate to polylactic acid is 1-2:1-2.

8. The preparation method according to claim 1, characterized in that: In the step S12, the mixing method is stirring for 30-60 minutes, ultrasonic dispersion for 30-60 minutes, and magnetic stirring for 30-60 minutes at room temperature.

9. The preparation method according to claim 1, characterized in that: In the step S13, the microfluidic spinning is followed by drying at room temperature.

10. A polyhydroxyalkanoate fiber prepared by the preparation method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Superfine fibre porous membrane material and preparation method thereof

    CN101327345A

  • High-elasticity PHA porous fiber material and preparing method thereof

    CN104452107A

  • Preparation method of composite electro-spun tissue engineering scaffold material, engineering scaffold material and application thereof

    CN111188102A

  • Special-shaped modified bio-based polymer fiber and preparation method thereof

    CN111349982A

  • Preparation method and application of polylactic acid hollow fiber aerogel

    CN116103774A